Loading Pitch, La Brea, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
Photo of the Brighton Pier at La Brea, Trinidad. An aerial tramway is used to carry pitch which is loaded onto ships docked by the pier.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Piers--Trinidad and Tobago; Seashore--Trinidad and Tobago; Aerial tramways--Trinidad and Tobago; Transportation--Trinidad and Tobago; Pitch; Cities and towns--Trinidad and Tobago--La Brea